Effect of small corner radius in cold punching of 22MnB5 die-quenched boron steel sheets - Hasnulhadi, Jaafar; Liyana, Tajul; Mohd, Zamzuri; Zailani Zainal, Abidin; Muhamad Nasir, Murad; Zamzuri, Hamedon (Institution of Engineering and Technology, 2022)
The effect of small corner radius in punching process of ultra-high strength category of steel i.e. 22MnB5 die-quenched boron steel was investigated. Although the die-quenched steel sheet can reach superior strength of above 1500 MPa, the ductility of the steel sheet is low, making punching process totally challenging. Punching of hole at 22MnB5 boron steel commonly carried out in hot condition prior to die-quenching and usually needed for complex tools for preheating, punching, transferring, and cooling the part. Inaccurate of hole dimension after quenching is inevitable due to the change of grain structure during cooling. In this study, a pre-hardened 22MnB5 boron steel sheet is punched under a small clearance in a normal cold condition. The small corner radius disperses the stress concentration at the punch edge and thus increases the material flow during initial stage of the punch penetration. The action of small clearance between punch and die reduce the tensile stress and therefore, the initiation of crack is delayed. The quality of the sheared edge surface was improved with the high percentage of area cover with the burnished surface.